1990
DOI: 10.1002/1097-4679(199007)46:4<507::aid-jclp2270460420>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The construct validity of an aftereffect-based subtyping system for alcoholics

Abstract: In an earlier project, we identified five alcohol‐consumption aftereffect factors, which were named Hangover, Euphoria, Flushing, Seizures, and Sleepiness. In this study (N = 100) we assessed the construct validities of the five, using 47 MMPI, self‐report, and recidivism criteria. The number of significant relationships between the factors and the criteria substantially exceeded chance. The Hangover factor related to social maladjustment and to the MMPI Psychopathic Deviate, Paranoia, Psychasthenia, Hypomania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Those patients who still exhibited depressive symptoms at the end of treatment were best distinguished from those who recovered by the first group's use of ethanol for social facilitation. This is consistent with the correlation between severity of hangover and social maladjustment found by Watson et al [50].…”
Section: Attitude and Moodsupporting
confidence: 93%
See 2 more Smart Citations
“…Those patients who still exhibited depressive symptoms at the end of treatment were best distinguished from those who recovered by the first group's use of ethanol for social facilitation. This is consistent with the correlation between severity of hangover and social maladjustment found by Watson et al [50].…”
Section: Attitude and Moodsupporting
confidence: 93%
“…He cites a number of studies which provide support for the hypothesis that persons classified as introverts experience a smaller effect from depressant drugs than do extraverts. A broad study of personality and alcoholism [50], found that the severity of hangover symptoms was related to social maladjustment. This complicates any supposed interaction with personality, and clear evidence of a relationship of broad personality factors to hangover has not emerged.…”
Section: Personalitymentioning
confidence: 99%
See 1 more Smart Citation